PENDAMPINGAN PENERAPAN METODE BERMAIN PERAN DALAM SEBUAH DRAMA - Napratilora, Martina; Mardiah; Sri Erdawati (Zhata Institut, 2024)
The aims of this service is to improve collage students skill in playing a drama using role playing method. This activity involve three lecturers and PGMI Students of STAI Auliaurrasyidin Tembilahan. The service structured is presenting the material, and practice together in applying it. The result show that collage student knowledge and skill in playing a drama are improving, like in the aspects of using facial expression. However, it gives positive effects , this event need continuously accompaniment, evaluation and sometimes can invite special drama tutor to increase students’ motivation or spirit in mproving their skill in a drama. It is hoped that the service result can give positif contribution in improving the skill and quality of students in playing a drama in STAI Auliaurrasyidin Tembilahan